Nutrient Expert Improves Nitrogen Efficiency and Environmental Benefits for Winter Wheat in China. (1st March 2018) - Zhang, J. J.; He, P.; Xu, X. P.; Ding, W. C.; Ullah, S.; Wang, Y. L.; Jia, L. L.; Cui, R. Z.; Wang, H. T.; Zhou, W.
Abstract : Core Ideas: Nutrient Expert is a new nutrient management approach and is confirmed for use in north‐central China. The continual feasibility of Nutrient Expert was evaluated through multiple‐point field experiments. This is the first report of Nutrient Expert on improving environmental benefits of winter wheat. Over application of N and P and poor nutrient management have become a common practice on the North China Plain, and lead to low nutrient use efficiency (NUE) and serious environmental problems. Thus, nutrient management for crops must be improved. In this study, 315 field experiments were conducted from 2011 to 2014 in major winter wheat domains in north‐central China to validate the continual feasibility of the Nutrient Expert (NE) system for improving NUE and reducing greenhouse gas (GHG) emission. The NE system significantly increased grain yield, profitability, and NUE, and decreased GHG emission. Compared with farmers' practice (FP), the NE treatment reduced N and P inputs by 41.4 and 30.1% (115 kg N ha −1 and 36 kg P2 O5 ha −1 ), respectively, and increased K input by 51.5% (25 kg K2 O ha −1 ). Compared with the FP and soil testing (ST) treatments, the NE treatment increased agronomic efficiency of nitrogen (AEN) by 70.0 and 13.3%, recovery efficiency of nitrogen (REN) by 73.8 and 13.3%, and partial factor productivity of nitrogen (PFPN) by 58.5 and 22.2%, respectively. Compared with the FP and ST treatments, the NE treatment reduced total N2 O emissions by 54.8 and 26.3%, total GHG emissions by 44.8 and 22.9%, and GHG emission intensity by 45.8 and 22.0%, respectively. These results confirmed that NE is an effective method to make fertilizer recommendations for wheat in north‐central China and has the potential to improve yield, NUE, and profitability, with low environmental pollution.